2017
DOI: 10.1055/s-0037-1608773
|View full text |Cite
|
Sign up to set email alerts
|

Who Is Safe to Extubate in the Neuroscience Intensive Care Unit?

Abstract: Patients admitted to the neuroscience intensive care unit (NICU) may have respiratory compromise from either central or peripheral neurological pathology, and may hence require intubation and mechanical ventilation for very diverse reasons. Liberation from invasive ventilation, that is, extubation, at the earliest possible time is a widely accepted principle in intensive care. For this, classic extubation criteria have been established in the general critical care setting, mainly targeting pulmonary function a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Many attempts have been made to identify predictors of extubation failure or success in neurocritically ill patients, and to establish extubation scores for neuro-ICU populations, but results remain controversial. 11 This is critical, as delayed extubation in neuro-ICU patients not meeting established extubation criteria leads to increasing complications, including VAP and prolonged ICU stay, while earlier and later extubated patients do not differ regarding reintubation rates. 12 We aimed to investigate the frequency of mechanical ventilation in adult patients in SE and its clinical associations, to identify early predictors at SE onset of prolonged postictal mechanical ventilation after SE, and to determine the associated outcomes of prolonged postictal mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…Many attempts have been made to identify predictors of extubation failure or success in neurocritically ill patients, and to establish extubation scores for neuro-ICU populations, but results remain controversial. 11 This is critical, as delayed extubation in neuro-ICU patients not meeting established extubation criteria leads to increasing complications, including VAP and prolonged ICU stay, while earlier and later extubated patients do not differ regarding reintubation rates. 12 We aimed to investigate the frequency of mechanical ventilation in adult patients in SE and its clinical associations, to identify early predictors at SE onset of prolonged postictal mechanical ventilation after SE, and to determine the associated outcomes of prolonged postictal mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…Another common source of uncertainty when preparing for potential DFE is the patient with a depressed neurologic status, whether it be from intracranial pathology such cerebral vascular accidents (CVA), traumatic brain injury (TBI), toxic metabolic encephalopathy, or those with peripheral neuromuscular disorders. In fact, it's estimated that DFE rate in neuroscience-ICU (NICU) may be as high as 20–40% [41]. These patients may have appropriate respiratory mechanics, but when extubated demonstrate an inability to protect their airways [41,42 ▪ ,43–45].…”
Section: Defining the Problem Of The Failed Or Difficult Extubationmentioning
confidence: 99%
“…In fact, it's estimated that DFE rate in neuroscience-ICU (NICU) may be as high as 20–40% [41]. These patients may have appropriate respiratory mechanics, but when extubated demonstrate an inability to protect their airways [41,42 ▪ ,43–45]. In a recent meta-analysis, Wang et al [45] demonstrated that there are additional factors that predispose neurologically injured adults to DFE – the absence of a gag reflex, lower Glasgow Coma Scale (GCS) (7–9T), duration of MV >24 h, thick secretions, or coexisting pulmonary disease.…”
Section: Defining the Problem Of The Failed Or Difficult Extubationmentioning
confidence: 99%
“…Unfortunately, those widespread criteria cannot easily be extrapolated to neurocritical patients. EF rates in neurological intensive care unit (NICU) studies are reported to range up to 40% 12 14 . Moreover, NICU patients show longer duration of ventilation and have higher rates of ventilator-induced pneumonia and mortality compared to general ICU populations 15 17 .…”
Section: Introductionmentioning
confidence: 99%